COMPARATIVE ANALYSIS OF THE PHRASEMAES OF ABDURAHMAN JAMI’S "TUHFAT UL-AHROR" AND ALISHER NAVOI’S "HAYRAT UL-ABROR" EPICS - Djalilova Kamola Erkin qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In Uzbek linguistics, A. Nurmanov for the first time raised the issue of modeling on the example of syntactic units of the Uzbek language. He argued that the starting point for a systematic study of syntax should be the syntactic model. A generalized structural scheme realized through real sentences is a syntactic model. There are two principles for defining syntactic models: the first is to determine the minimum structure sufficient to be a predicative unit; the second principle is to identify the structural elements that serve to ensure not only grammatical integrity but also semantic completeness. Phraseological units can also be syntactically modeled.